2012
DOI: 10.1111/j.1468-2257.2011.00578.x
|View full text |Cite
|
Sign up to set email alerts
|

Neoliberalism and the Urban Economy in Ghana: Urban Employment, Inequality, and Poverty

Abstract: Ghana is one of a few African countries where more people now reside in cities than in the countryside. What is not as well-known are the changes that have taken place in the economic base of Ghanaian cities. This paper tells that story. It focuses particularly on jobs, incomes, inequality, and poverty, and their characteristics in an era when neoliberal policies have been implemented. It draws on census reports, national surveys, and published reports in order to overcome the dearth of information about the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…In response to Ghana's economic woes in the 1980s, a situation that had been exacerbated by the oil crises of the 1970s, the country undertook an Economic Recovery Programme in 1983, and acting on the recommendation of Bretton Woods institutions (e.g., World Bank), implemented a structural adjustment programme, in order to stimulate and sustain economic growth in the country. These economic programmes facilitated the mainstreaming of neoliberalism, and according to [59] (p. 89), "the political precept of neoliberalism is that, while all essential collective decisions need to include the constitutional State, State intervention in the social and economic life should generally be minimal. Rather, the role of the State should be primarily to guarantee and ensure freedom of individual economic agents".…”
Section: Globalisation and Neoliberalismmentioning
confidence: 99%
“…In response to Ghana's economic woes in the 1980s, a situation that had been exacerbated by the oil crises of the 1970s, the country undertook an Economic Recovery Programme in 1983, and acting on the recommendation of Bretton Woods institutions (e.g., World Bank), implemented a structural adjustment programme, in order to stimulate and sustain economic growth in the country. These economic programmes facilitated the mainstreaming of neoliberalism, and according to [59] (p. 89), "the political precept of neoliberalism is that, while all essential collective decisions need to include the constitutional State, State intervention in the social and economic life should generally be minimal. Rather, the role of the State should be primarily to guarantee and ensure freedom of individual economic agents".…”
Section: Globalisation and Neoliberalismmentioning
confidence: 99%
“…Also, not only are government investments lacking in the three northern regions, private investments appear to track government investments. Obeng‐Odoom () for example, observed that while the Greater Accra region with a lot of basic public services attracted the most private sector investments from 2001 to 2009, the Upper West region that lacked public services had only one private investment during the same period. Numerous explanations including very limited colonial and postcolonial state investments, high labor migration rates, low agro‐ecological potential, and poor market access have been offered (Whitehead ) but much remains to be done to bridge the north‐south disparities in socioeconomic development, with profound implications for children's nutritional outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the dominance of urban politics and neo-liberal urbanism hinders the potential of urban policies to stimulate transformative change in the context of sustainability, as in most cases, the priorities of political actors shape the potential of these policies to deliver transformative sustainability change. In this context, according to [23] (p. 89), "the political precept of neoliberalism is that, while all essential collective decisions need to include the constitutional State, State intervention in the social and economic life should generally be minimal. Rather, the role of the State should be primarily to guarantee and ensure freedom of individual economic agents".…”
Section: Literature Reviewmentioning
confidence: 99%